Analisis Fleksibilitas Strategis Perkembangan Usaha Kilang Batu Bata Pasca Pandemi COVID-19 (Studi Kasus: Kota Banda Aceh) - Ijal Fahmi; Ilyas Ilyas (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2021)
The specific objectives of this research are; 1) To find out the development of production, working capital, labor, sales volume, wage level, selling price, material costs, and profits of brick industry business actors, 2) To determine the feasibility of brick business in Banda Aceh City, and 3) To analyze strategic flexibility in the development of the brick refinery business after the COVID-19 pandemic. Descriptive and quantitative analysis was used to analyze the data, with direct observation of a research object in order to determine the condition of the business location and the characteristics of the brick business in Banda Aceh City. In order to determine whether or not the business was feasible, the business was carried out using BCR analysis calculations. Based on the results of research and discussion, it can be concluded that the development of the brick refinery business is known. The results of data analysis regarding the amount of production, labor, working capital, sales volume, wages, selling prices, raw material costs, and business profits of the brick refinery have increased every year. In contrast, in 2020-2021 there will be a decline caused by declining demand and high raw materials for brick processing. The results of the calculation of business feasibility in terms of Capital and Revenue using the BCR formula show that the capital and revenue variables have a positive effect on the feasibility of the 2017 to 2019 Brick Refinery Business or in other words that the Brick Refinery Business does not lose. It was reversed in 2020-2021 where the brick business decreased in demand but the stock became large and no significant losses were found. However, the bricks business revenue has decreased. The brick refinery business seen from the marketing aspect experienced positive developments in 2017-2019, this can be seen from the number of requests that always increase every year. It is different in 2020-2021 where the development from the marketing aspect is low, due to the pandemic and reduced development in Banda Aceh City.